Activities of fisheries co-operative societies in India to boost up and optimise the resources and economy of farmers: a review - Sanyal, Tanmay; Saha, Aloke; Mukherjee, Pronoy (Journal of Fisheries, 2023)
Fisheries within India have significant financial, nutritional and socio-economic development prospects. The country has a diversified natural fishery resource. Fishermen have continuously undertaken fisheries activity throughout the country over decades and fisheries co-operatives have now been developed for cumulative production and effective regulation of fishery activities. It was observed that there have been many inconsistencies, mostly in the management of fisheries co-operatives; a few were effectively handled under active supervision and government backing, whereas many co-operatives are facing various problems for their existence. Effective administration of fisherman’s co-operatives is critical for increasing fishing productivity and the socio-economic growth of fishermen. Co-operatives can help fishermen develop their skills and gather information about technology, marketing, and management. Co-operatives can improve productivity, processing, storing and transportation capabilities while also meeting financial demands. As a result, co-operative organisations may contend with multinational corporations by integrating competent management abilities with co-operative power. To do this, a nationwide research project focusing on different elements of fisheries co-operatives is recommended. The need for appropriate policy implications for such sustainable management of fisheries co-operatives in accordance with current technical advancements in the sector of aquaculture, environmental degradation and global warming has been highlighted.